Teologi Liberalisme: Antara Cita-Cita dan Realita - Aswadi Aswadi (Universitas Islam Negeri Mataram, 2009)
The aim of liberal theology was, basically, to promote the freedom of thought. However, it also can be trapped into an authoritarian system leading to tyranny when the aim is forced. It was true in the case of Mu’tazilite, a sect that is considered the symbol of liberalism in Islamic theology. The sect, in one side, campaigned freedom of thought, but in other side, it also applied mihnah, a tool of measuring the state theology. Yet, when mihnah was applied, the people had no freedom, even the caliph also participated to impose the idea that the Qur'an was created. As a result of the implementation of mihnah, there was the emergence of a gap, prolonged anxiety and tension among the Islamic society. Hence, their opponents increased which in turn encouraged the Caliph al-Mutawakkil to launch a new policy to cancel the mihnah, then ordered the people to follow muhadditsīn, the majority people believing in the Hadits, as well as a forerunner to the birth of the term ahl al-Sunna wa al-Jama’a.